1998
DOI: 10.1002/hep.510270306
|View full text |Cite
|
Sign up to set email alerts
|

Splenic impedance indices: A useful method to monitor patients after liver transplantation?

Abstract: Splenic Doppler impedance indices are influenced, in portal hypertensive patients, by the resistance of the portal system. The aim of the study was to verify the usefulness of these indices in evaluating the presence of a pathological increase in portal resistance in patients with complications after liver transplantation. Splenic impedance indices have been evaluated in 46 patients before orthotopic liver transplantation (OLT), and 2 days, 1, 4, 8, and 12 to 18 months after transplantation. The results showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
10
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 31 publications
2
10
0
Order By: Relevance
“…16 One possible factor contributing to this abnormality could be the patency of portosystemic collateral vessels, which have been demonstrated to persist long after transplantation 35 and provide a low-resistance downstream pathway for mesenteric flow. The persistent spleen enlargement after OLT, also described by previous studies, 13,35 might also contribute to the maintenance of the collateral circulation patent and vice versa. However, such portosystemic connection alone cannot fully justify a splanchnic hyperkinetic circulation in the absence of an increased cardiac output, as it was in our case.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…16 One possible factor contributing to this abnormality could be the patency of portosystemic collateral vessels, which have been demonstrated to persist long after transplantation 35 and provide a low-resistance downstream pathway for mesenteric flow. The persistent spleen enlargement after OLT, also described by previous studies, 13,35 might also contribute to the maintenance of the collateral circulation patent and vice versa. However, such portosystemic connection alone cannot fully justify a splanchnic hyperkinetic circulation in the absence of an increased cardiac output, as it was in our case.…”
Section: Discussionsupporting
confidence: 65%
“…Other hemodynamic consequences are observed in the splanchnic arterial system, in particular in the splenic, hepatic, and superior mesenteric arteries. [12][13][14][15][16][17] In the two former arterial districts, Doppler impedance indices correlate with portal resistance, 12,17 while in the latter, their reduction likely reflects the splanchnic hyperkinetic circulation. To our knowledge, very few studies have been focused on the splanchnic hemodynamic changes occurring in liver transplant recipients.…”
mentioning
confidence: 99%
“…The decrease of pulsatility index in the superior mesenteric artery in established cirrhosis therefore indicates the presence of vasodilation (15), which is hypothesized to be caused by circulating vasoactive agents (16)(17)(18). Impedance indexes in the splenic artery have been reported to be strictly related to transhepatic portal resistance (19) and to re ect its changes in pathological conditions or after surgery (10,11). Contrary to this, the mechanisms underlying the alteration of hepatic artery Doppler impedance indexes are still a matter of debate, but are generally attributed to the hepatic architectural distortion (7)(8)(9)20).…”
mentioning
confidence: 96%
“…On average, portal velocity is not reduced in chronic hepatitis, but it has been reported to be statistically slower in chronic hepatitis with pronounced brosis than in chronic hepatitis with little brosis (6). In recent years, the exploration of splanchnic arteries has provided new information on portal hypertension and has demonstrated that Doppler impedance indexes are increased in both the hepatic artery (7)(8)(9) and the splenic artery (10,11) and decreased in the superior mesenteric artery (12). Doppler impedance indexes derive from the Doppler spectrum and allow an indirect estimate of the downstream vascular resistance in compliant systems with a pulsatile ow, such as blood vessels (13,14).…”
mentioning
confidence: 99%
“…It can define the velocity and characteristics of blood flow within the portal system and the hepatic and splenic arteries [2,13]. Previous studies have shown that portal vein flow velocity [14,[15][16][17][18] and resistance index of the hepatic [1,14,[20][21][22] and splenic artery [21,[23][24][25][26] mirror the severity of portal hypertension in patients with cirrhosis. Given these observations, DUS is routinely used in the follow-up of patients with cirrhosis.…”
Section: Introductionmentioning
confidence: 99%